Comparison of cadmium levels in quail feed and eggs by atomic absorption and inductively coupled plasma - Santisteban-Rojas, Oscar-Pedro (2022)
The consumption of quail eggs in Peru is on the rise, the egg can store significant concentrations of metal ions. The present investigation sought to determine the cadmium concentration in both yolk, white, feed and quail eggs and to correlate its possible contamination with the feeding of the birds. For this, the wet mineralization of the sample was carried out using concentrated HNO3: HCl and ion cleaners. The solutions were analyzed by Atomic Absorption (AA) and Inductive Coupling Plasma (ICP) obtaining 0,136±0,040 and 0,034±0,010; 0,158±0,060 and 0,012±0,002; 0,364±0,010 and 0,095±0,010; 0,020±0,005  and  0,008±0,001;  0,017±0,005  and  0,001±0,000 ppm in yolks, whites, feed, supermarkets and ambulatory sales, respectively. Yolks were found to contain more cadmium than whites, feed is an important source of cadmium for poultry, in supermarket and outpatient samples the contents are similar. ICP analysis detects lower concentrations in samples.